MF59- and Al(OH)3-Adjuvanted Staphylococcus aureus (4C-Staph) Vaccines Induce Sustained Protective Humoral and Cellular Immune Responses, with a Critical Role for Effector CD4 T Cells at Low Antibody Titers - Monaci, Elisabetta; Mancini, Francesca; Lofano, Giuseppe; Bacconi, Marta; Tavarini, Simona; Sammicheli, Chiara; Arcidiacono, Letizia; Giraldi, Monica; Galletti, Bruno; Rossi Paccani, Silvia; Torre, Antonina; Fontana, Maria Rita; et al. (Frontiers in Immunology, 2015)
Staphylococcus aureus (S. aureus) is an important opportunistic pathogen that may cause invasive life-threatening infections like sepsis and pneumonia. Due to increasing antibiotic-resistance, the development of an effective vaccine against S. aureus is needed. Although a correlate of protection against staphylococcal diseases is not yet established, several findings suggest that both antibodies and CD4 T cells might contribute to optimal immunity. In this study, we show that adjuvanting a multivalent vaccine (4C-Staph) with MF59, an oil-in-water emulsion licensed in human vaccines, further potentiated antigen-specific IgG titers and CD4 T cell responses compared to alum and conferred protection in the peritonitis model of S. aureus infection. Moreover, we showed that MF59- and alum-adjuvanted 4C-Staph vaccines induced persistent antigen-specific humoral and T cell responses, and protected mice from infection up to 4 months after immunization. Furthermore, 4C-Staph formulated with MF59 was used to investigate which immune compartment is involved in vaccine-induced protection. Using CD4 T cell-depleted mice or B cell deficient mice, we demonstrated that both T and B cell responses contributed to 4C-Staph vaccine-mediated protective immunity. However, the role of CD4 T cells seemed more evident in the presence of low antibody responses. This study provides preclinical data further supporting the use of the adjuvanted 4C-Staph vaccines against S. aureus diseases, and provides critical insights on the correlates of protective immunity necessary to combat this pathogen.